2016
DOI: 10.1111/hex.12496
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for patients and their relatives in escalating clinical deterioration in hospital? A systematic review

Abstract: BackgroundMeasures exist to improve early recognition of, and response to, deteriorating patients in hospital. However, deteriorating patients continue to go unrecognized. To address this, interventions have been developed that invite patients and relatives to escalate patient deterioration to a rapid response team (RRT).ObjectiveTo systematically review articles that describe these interventions and investigate their effectiveness at reducing preventable deterioration.Search strategyFollowing PRISMA guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…Further supporting the concept of parent escalation of care, there was agreement C4H provided an added safety net for early recognition of deterioration that parents can recognize what is not normal for their child and can notice subtle changes that nurses and doctors may not detect . This parent role has yet to be evaluated in practice …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further supporting the concept of parent escalation of care, there was agreement C4H provided an added safety net for early recognition of deterioration that parents can recognize what is not normal for their child and can notice subtle changes that nurses and doctors may not detect . This parent role has yet to be evaluated in practice …”
Section: Discussionmentioning
confidence: 99%
“…How family involvement in Rapid Response Systems has been implemented and evaluated in the USA and UK context was the focus of three recent reviews. Evaluations reported uniformly positive family satisfaction .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous original studies have yielded multidimensional findings regarding diverse aspects of PFE in patient safety, such as the effects of PFE interventions on specific types of adverse events (Cox et al, ; Davis, Sevdalis, Pinto, Darzi, & Vincent, ; Jha et al, ), factors affecting PFE (Larsson, Sahlsten, Segesten, & Plos, ; Martin, Navne, & Lipczak, ; Mohsin‐Shaikh, Garfield, & Franklin, ), benefits and harms of PFE (Etchegaray et al, ; Latimer, Chaboyer, & Gillespie, ; Weingart et al, ) and perspectives of HCPs and PFs (Latimer et al, ; Skagerström, Ericsson, Nilsen, Ekstedt, & Schildmeijer, ). Several reviews have attempted to address information overload and the inconsistent results of these studies, but they have mostly focused on specific issues such as the role of PFs in patient safety (Albutt, O'Hara, Conner, Fletcher, & Lawton, ) and factors influencing PFE implementation (Berger, Flickinger, Pfoh, Martinez, & Dy, ; Hall et al, ; Longtin et al, ; Trier, Valderas, Wensing, Martin, & Egebart, ). Only one comprehensive review has employed data searching and that was performed back in 2008 (Schwappach, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these initiatives being widely publicized, there remain few reports about their implementation or evaluation. Three reviews found 14 reports describing implementation of family escalation of care processes in the United States of America (US) and United Kingdom (UK) contexts. Key findings were that family feedback was uniformly positive, and in particular, families were happy that there was a process in place for them to voice concerns irrespective of whether or not they initiated escalation of care .…”
Section: Introductionmentioning
confidence: 99%